Fish Logistic System Using Value and Cold Chain Approaches - Arius Kambu; Charley M Bisay (Universitas Cenderawasih, 2023)
The purpose of this study was to solve the poverty issues prevalent in local fishers’ households in the Biak Archipelago, Indonesia. The Value and Cold Chain approaches were used to determine the Government's mandate through Regulation of the Minister of Marine Affairs and Fisheries Number 5 of 2014 on the National Fish Logistics System. This regulation is supported by Presidential Instruction Number 7 of 2016 on accelerating the development of the fishing industry, though limited to socialization in the Biak Islands. The Case study research approach and normative analysis were tested using Porter's theory of value chains. The results showed that the logistics system in the upstream and downstream flow of goods and information was not implemented. Furthermore, the Government focused on appointing third parties to operationalize the Cold Chain and the low competence of human resources to organize and manage the fisheries sector.